Two cases of breast carcinoma with osteoclastic giant cells: Are the osteoclastic giant cells pro-tumoural differentiation of macrophages? - Shishido-Hara Yukiko; Kurata Atsushi; Fujiwara Masachika; Itoh Hiroki; Imoto Shigeru; Kamma Hiroshi (BMC, 2010)
Abstract Breast carcinoma with osteoclastic giant cells (OGCs) is characterized by multinucleated OGCs, and usually displays inflammatory hypervascular stroma. OGCs may derive from tumor-associated macrophages, but their nature remains controversial. We report two cases, in which OGCs appear in common microenvironment despite different tumoural histology. A 44-year-old woman (Case 1) had OGCs accompanying invasive ductal carcinoma, and an 83-year-old woman (Case 2) with carcinosarcoma. Immunohistochemically, in both cases, tumoural and non-tumoural cells strongly expressed VEGF and MMP12, which promote macrophage migration and angiogenesis. The Chalkley count on CD-31-stained sections revealed elevated angiogenesis in both cases. The OGCs expressed bone-osteoclast markers (MMP9, TRAP, cathepsin K) and a histiocyte marker (CD68), but not an MHC class II antigen, HLA-DR. The results indicate a pathogenesis: regardless of tumoural histology, OGCs derive from macrophages, likely in response to hypervascular microenvironments with secretion of common cytokines. The OGCs have acquired bone-osteoclast-like characteristics, but lost antigen presentation abilities as an anti-cancer defense. Appearance of OGCs may not be anti-tumoural immunological reactions, but rather pro-tumoural differentiation of macrophage responding to hypervascular microenvironments induced by breast cancer.